2005
DOI: 10.1097/01.hjh.0000179908.51187.de
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment and control of hypertension in Portugal: the PAP study

Abstract: Our results indicate that hypertension is highly prevalent in Portugal. The percentages of those with hypertension that are aware, treated and controlled are unacceptably low. These results underscore the urgent need to develop national strategies to improve prevention, detection and treatment of hypertension in Portugal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
89
10
23

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(144 citation statements)
references
References 16 publications
22
89
10
23
Order By: Relevance
“…17 In particular, the lack of improvement in SBP may prevent the patients to receive the benefits of otherwise improved hypertension care. Compared with the prevalences of hypertension in our study, those reported since 2000 in other studies by age and sex have been lower in most, [18][19][20][21][22][23][24][25][26][27] but not in all populations. 27,28 As in our paper, the rate of awareness of hypertension in these reports was usually more than 60%.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…17 In particular, the lack of improvement in SBP may prevent the patients to receive the benefits of otherwise improved hypertension care. Compared with the prevalences of hypertension in our study, those reported since 2000 in other studies by age and sex have been lower in most, [18][19][20][21][22][23][24][25][26][27] but not in all populations. 27,28 As in our paper, the rate of awareness of hypertension in these reports was usually more than 60%.…”
Section: Discussioncontrasting
confidence: 91%
“…Exceptions to this rule include a low awareness and control rates among men and women in China 21 and men in Portugal. 25 Data on trends of hypertension care for international comparison published after JNC V 11 in the older adults are scarce. An increasing trend in the prevalence of hypertension was observed in mainland China, in an urban population in Chile 23 in both men and women, and in Taiwan in men.…”
Section: Discussionmentioning
confidence: 99%
“…In other countries, researchers found higher prevalence compared to the present one: in China, in 1998, it was 24% among men aged 35-59 years, 20 and in Portugal, in 2003, prevalence in adults aged 20-90 years was 42%, being 26% among those aged 20-35 years. 16 Prevalence of arterial hypertension in military subjects who practice physical activity inside the military quarters is half of that observed in military subjects who do not practice it. This may be explained by the regularity and intensity with which physical activities are practiced in the military quarters, besides being a directed and supervised activity, characteristics that are necessary in order to produce some effect on blood pressure.…”
Section: Discussionmentioning
confidence: 98%
“…Hypertension is a risk factor for all cardiovascular disease, but mainly for stroke. Its prevalence in Portugal in 2003 was 50% in men and 39% in women [29], similar or lower than many European countries [30]. Levels of control of hypertension are low (7% for men and 11% for women [29]) and it is possible that these issues have greater relevance for Africans, particularly poor Africans, than those born in Portugal.…”
Section: Effect Of Class and Marital Status On Mortality Of Cape Verdmentioning
confidence: 90%